1984
DOI: 10.1088/0029-5515/24/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of fusion

Abstract: The safety aspects of fusion have been attracting increasing attention in the research and development programmes of various countries. The paper summarizes the results of the safety investigations of recent years. The expected inventories of tritium and activation products in fusion reactors are defined. The potential for release of radioactivity under operational and accident conditions is reviewed. Concerns regarding accidents with coolant transients, plasma disruptions and chemical reactions of breeder mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Between 20 and 30% of radioactivity in the structural materials is associated with the first wall; and over 95% of it is in the first-wall/blanket components [69], The relative concentration of radioactivity in various candidate structural materials is shown in Figs. 10 and 11 [70]. It is clear that several materials provide a lower inventory of radioactivity than stainless steel; most notably the V-20% Ti alloy and the SiC ceramic which can be termed a low-activation material.…”
Section: Activation Products Of Fusion Reactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 20 and 30% of radioactivity in the structural materials is associated with the first wall; and over 95% of it is in the first-wall/blanket components [69], The relative concentration of radioactivity in various candidate structural materials is shown in Figs. 10 and 11 [70]. It is clear that several materials provide a lower inventory of radioactivity than stainless steel; most notably the V-20% Ti alloy and the SiC ceramic which can be termed a low-activation material.…”
Section: Activation Products Of Fusion Reactorsmentioning
confidence: 99%
“…11. Radioactivity for reactors after two years of typical operation [70]. STARFIRE is a fusion reactor; the first wall and blanket structures from aluminum, steel and SiC.…”
Section: Activation Products Of Fusion Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies carried out during the past decade (see, e.g., Kazimi, 1984: ESECOM, 1989: Conn et al, 1990 have shown that even if the design of the first wall and blanket is based on the existing structural materials like stainless steel, then the induced radioactivity in a reactor-tokamak is still a few times less than in a fission reactor of a comparable power. This can be illustrated by Fig.…”
Section: Time After Shutdown (S)mentioning
confidence: 99%